2015
DOI: 10.18006/2015.3(2).174.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laurus nobilis extract on the functioning of liver against ccl4 induced toxicity

Abstract: KEYWORDS Laurus nobilis Biochemical markers CCl4Hystochemistry Toxic hepatitis ABSTRACTIn present study effect of laurel leaf extract (Laurus nobilis) on biochemical parameters and histomorphology of rat liver induced by toxic damage of CCl4 was studied. Introduction of CCl4 in animals was always carried out in fatal to 36 hours. A single injection of the L. nobilis extract ssimultaneously with CCl4 leads to 100% survivability. To evaluate the degree of hepatocyte damage in experimental modeling hepatitis de R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…This study revealed that Bay leaf improving lipid profile by decreasing the levels of TC, TG, LDL-C and VLDL-C in serum. This conclusion are in agreement with Gasparyan et al who mentioned that extract of Bay leaf leading to decrease serum TC and TG in male Wistar rats undergoes induced toxicity liver [9] . Also, agreed with Casamassima et al who showed the Bay leaf recovering lipid profile in hyperlipidemic rabbits [12] .…”
Section: Figure 1: Effect Of Bay Leaf and Its Isolated Flavonoids And...supporting
confidence: 93%
See 1 more Smart Citation
“…This study revealed that Bay leaf improving lipid profile by decreasing the levels of TC, TG, LDL-C and VLDL-C in serum. This conclusion are in agreement with Gasparyan et al who mentioned that extract of Bay leaf leading to decrease serum TC and TG in male Wistar rats undergoes induced toxicity liver [9] . Also, agreed with Casamassima et al who showed the Bay leaf recovering lipid profile in hyperlipidemic rabbits [12] .…”
Section: Figure 1: Effect Of Bay Leaf and Its Isolated Flavonoids And...supporting
confidence: 93%
“…Bay leaf contains many types of flavonoids and glycosides, such as kaempferol, quercetin, apigenin, luteolin, quercetin 3-O-α-Lrhamnopyranoside, kaempferol-3-O-βglucopyranoside, quercetin-3'-O-β-glucopyranoside, quercetin-3-O-β-galactoside, isorhamnetin-3-O-βglucopyranoside, isorhamnetin-3-O-βgalactopyranoside, quercetin-3-O-rutinoside, kaempferol-3-O-rutinoside, isorhamnetin-3-Orutinoside and isorhamnetin [1,5] . Bay leaf has a broad range of biological properties including, antimicrobial [6] , anti-inflammatory [2] , anti-fungal [7] , improves blood lipids profile [8] , improves liver function [9] and having antioxidant properties [10] . The aim of the present study is to characterize the effect of Bay leaf and its isolated flavonoids and glycosides on the levels of total cholesterol (TC), triglycerides (TG), high density lipoproteins-cholesterol (HDL-C), low density lipoproteins-cholesterol (LDL-C) and very low density lipoproteins-cholesterol (VLDL-C) in the local Iraqi female rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an experimental study performed on rats showed that the methanol extract of L. nobilis at 400 mg/kg acts on the liver as a potent scavenger of free radicals to prevent the hepatotoxicity induced by paracetamol (Ravindran et al, 2013). Another in vivo study carried out by Gasparyan et al (2015) revealed that some phenolic compounds such as flavonoids and eugenol of L. nobilis protect hepatocytes of rats against metabolic and histological abnormalities induced by tetrachloromethane.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%